An Exploration of the Experience of Huntington's Disease in Family Dyads: An Interpretative Phenomenological Analysis. Issue 3 (10th November 2013) - Maxted, Caroline; Simpson, Jane; Weatherhead, Stephen
Abstract: Huntington's disease (HD) is a hereditary, late onset, neurodegenerative disorder. Children of affected parents have a 50 % chance of inheriting HD. Research into the psychological consequences of HD for the family has focussed on individual family members, but little is known about the ways in which its impact is jointly experienced by members of these families. This is particularly important due to the hereditary nature of HD. To address this, the current study examined the experiences of dyads within affected families. Seven parent/adult child dyads were interviewed jointly about their experiences and relationships with their family and each other and interpretative phenomenological analysis was used to analyse the resultant data. Identified themes were: "A spectre hanging over us": HD as a presence within the family, "Us against the world": Protection, knowledge and control, and "That could be me in 50 years": Cyclical changes in identity and role. These findings are examined in relation to previous research and indicate the need for an increased understanding of the needs of HD families. Clinical implications and suggestions for further research are discussed.